Household preferences for solid waste management in Malaysia - Jamal Othman; Economy and Environment Program for Southeast Asia. (Singapore EEPSEA, 2003)
This report analyses householders' attitudes to the delivery of solid waste management services in two areas of Malaysia. Using two environmenal valuation techniques, it finds that households highly value improvements in solid waste management and would be willing to pay a premium of up to 100% for more frequent collections and better transport and disposal methods. It also finds that residents would welcome recycling facilities but would not necessarily be willing to pay for them.
Includes bibliographical references and index.
Keywords: Integrated solid waste management -- Malaysia -- Public opinion; Recycling (waste, etc.) -- Malaysia -- Public opinion; Waste minimization -- Malaysia -- Public opinion; International Development Research Centre (Canada)